Acanthocephalan parasites in the striped mojarra (Eugerres plumieri) (Cuvier, 1830) of the Tamiahua Lagoon, Veracruz, Mexico Acantocéfalos parásitos de la mojarra rayada Eugerres plumieri (Cuvier, 1830) en la laguna de Tamiahua, Veracruz, México - Zarza Meza, Eduardo Alfredo; Alvarado, Juan Irvin Rodríguez; González, y Rodrigo Cuervo (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Striped mojarra is a species of great economic importance as is a fishing resource for which the object of this study is to determine what are major parasites which presents, for this is captured and analyzed a total of 105 copies of Eugerres plumieri of the month of October 2013 to the month of March 2014, with a sex ratio of females and 1.44:1 males, females with a size and weight average of 24.05 cm and 178.41 g and males 24,22 cm and 192.09 g, only 21. 9% of the total sample was found to be parasitized, registering 207 parasites, identifying to Octospiniferoides sp and Dollfusentis chandleri, females being the most parasitized by both species of acanthocephala. The rear segment of the intestine presented many parasites, followed by the segment average and above. In the month of October there was an increased presence of parasites (7.5 parasites per fish) and in February found no parasites. In terms of the parameters of infection Octospiniferoides sp presented the highest prevalence (21.90%), medium (1.68 parasites per fish) and mean abundance (7.69 parasites per fish). The species Dollfusentis chandleri had individuals with an average of 4.31 mm